Bridging Multiple Worlds of Immigrant, Indigenous, and Low-Income Students. Issue 1 (2nd April 2020) - Yamauchi, Lois A.; Cooper, Catherine R.
ABSTRACT: This symposium presents three studies that apply Bridging Multiple Worlds and other complementary theories to analyze how students and families engage their cultural resources to create multiple pathways to academic and life success. The studies focus on individuals from Native Hawaiian, Latinx, immigrant, and low-income backgrounds, groups traditionally marginalized in schools and society. The authors identify educational inequities and innovative ways that were employed to address them and advance social justice. These include efforts by Native Hawaiian educators to integrate Hawaiian culture into their instruction, the Padres Líderes (parent leaders) parent empowerment program, and Integrated Logic Models, a new tool for linking equity research, practice, and evaluation. The authors describe cultural resources that were strengths for students and their families and frame future research, practice, and policies that define academic and life success in ways that are more inclusive of these underserved populations.